The Effects of Statin and Niacin on Plaque Stability, Plaque Regression, Inflammation and Oxidative Stress in Patients With Mild to Moderate Coronary Artery Stenosis - Lee, Kyounghoon (The Korean Society of Cardiology, 2011)
BACKGROUND AND OBJECTIVES: The aim of this study was to compare the effects of a combination of niacin and simvastatin to simvastatin alone, on plaque regression and inflammatory makers. SUBJECTS AND METHODS: The study had a prospective, randomized design. Subjects were patients with intermediate coronary artery stenosis. A total of 28 patients received a combination of niacin 1,000 mg plus simvastatin 40 mg (N+S group, n=14); the other group received simvastatin 40 mg alone (S group, n=14). All patients had a baseline and a 9-month follow-up coronary angiogram and an intravascular ultrasound procedure. Parameters such as normalized total atheroma volume (nTAV) and percent atheroma volume (PAV) were analyzed before and after treatment as were inflammatory markers such as high sensitivity C-reactive protein (hs-CRP), Matrix me-talloproteinase-9 (MMP-9) and soluble CD40 ligand (sCD40L). RESULTS: There was no difference in baseline characteristics between the two groups. The nTAV and PAV in the N+S group before and after treatment were not different than those in the S group. But the degree of changes (delta) in nTAV in the N+S group was greater than that in the S group (-21.6±10.68 vs. 5.25±42.19, respectively, p=0.024). Also, the change in PAV in the NS group was higher than that in the S group (-1.2±2.5 vs. -0.6±5, respectively, p=0.047. Changes in hs-CRP, MMP-9, and sCD40L in the NS group were significantly greater than those of the S group (-0.71±1.25, 73.5±64.9, -1,970±1,925 vs. -0.32±0.96, 62.5±30.6, -1,673±2,628, respectively). CONCLUSION: The combination of niacin plus simvastatin decreases coronary plaque volume and attenuates the inflammatory response in patients with intermediate coronary artery stenosis.